2017
DOI: 10.1111/jphp.12772
|View full text |Cite
|
Sign up to set email alerts
|

Topotecan-loaded lipid nanoparticles as a viable tool for the topical treatment of skin cancers

Abstract: TPT-NLC-HEC may be a valuable tool for the topical treatment of skin cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…A first way to control the release profile of a drug from a cellulose-based material is to design the complete drug delivery system based on surface charge interactions. Pure hydrogels of cellulosics were used to entrap lipid nanoparticles loaded with 5-fluorouracil [56] and topotecan [53] (two hydrophilic chemotherapeutic agents active against carcinoma), avanafil [55] (a hydrophobic molecule active in erectile dysfunction) and nano-emulsified copaiba oil [54] (anti-inflammatory essential oil).…”
Section: Hydrogels As Lipid Nanoparticle Scaffoldsmentioning
confidence: 99%
See 2 more Smart Citations
“…A first way to control the release profile of a drug from a cellulose-based material is to design the complete drug delivery system based on surface charge interactions. Pure hydrogels of cellulosics were used to entrap lipid nanoparticles loaded with 5-fluorouracil [56] and topotecan [53] (two hydrophilic chemotherapeutic agents active against carcinoma), avanafil [55] (a hydrophobic molecule active in erectile dysfunction) and nano-emulsified copaiba oil [54] (anti-inflammatory essential oil).…”
Section: Hydrogels As Lipid Nanoparticle Scaffoldsmentioning
confidence: 99%
“…The study also showed that the anti-inflammatory effect of the complete system remained successfully equivalent to that of ketoprofen (a well-known non-steroidal anti-inflammatory drug). Venancio and collaborators [53] also pointed out that the neutral charge of HEC films encapsulating topotecan-loaded LNP allowed more of the lipid nanoparticles to be retained in the stratum corneum and in the deeper layers of the skin compared to LNP-loaded chitosan films. Because of its neutral charge, HEC polymer was then proven to have a wide range of application as LNP host.…”
Section: Hydrogels As Lipid Nanoparticle Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various nanoparticle-mediated drug delivery systems are recently being investigated to check the chemical stability and improve the release profile of the antitumour drugs like TPT [ 1 , 3 ]. These drug delivery systems include lipid-based nanoparticles [ 4 ], mesoporous silica nanoparticles [ 5 ], solid lipid nanoparticles (SLNs) [ 6 ], and liposomes [ 7 ]. However, most of these studies did not report the complete profile of TPT including its antitumour capability, therapeutic efficacy, and safety profile, most particularly after rectal administration.…”
Section: Introductionmentioning
confidence: 99%
“…The major limitation of this drug is that TPT is unstable in physiological conditions and undergoes a pH-dependent rapid and reversible hydrolysis from a closed lactone ring to the inactive carboxylated open-ring form, which causes the loss of the antitumor activity of the drug [4]. To protect TPT from hydrolysis, the encapsulation into different types of nanoparticles such as liposomes, lipid nanoparticles, and mesoporous silica has been presented [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%